Portable Water Quality Measurenment System for Sanitation - Muhamad Fauzan Zarkashie; Elvan Yuniarti; Ryan Rizaldy (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2022)
ABSTRACTWater is one of the essential needs that play an essential role in supporting life on earth. Water for sanitary hygiene purposes is used for several things to maintain individual hygiene, such as bathing and toothbrushes. Water is also for washing foodstuffs, tableware, and washing clothes. In addition, water for hygiene sanitation can be used as raw water for drinking water. This research designs a water quality measurement tool using parameters following water quality for sanitary hygiene purposes issued by the Ministry of Health. These parameters include turbidity, acidity (pH), temperature, and solids in water. The tool is designed to use Arduino Uno as a controller, sensors according to the parameters of photodiode sensors, pH, temperature, TDS (Total Dissolved Solids), and output systems using an LCD 20 x 4. This study concluded that the water quality detection system is running well, using photodiode sensors that can read each level of turbidity based on the value of ADC (Analog Digital Converter). The TDS sensor has an accuracy rate of 93.2% with a 6.8% error percentage. The pH sensor has an occurrence rate of 97.5% with a 2.5% error percentage, and a temperature sensor has an accuracy of 97.84% with a 2.16% error percentage.